2015
DOI: 10.4172/2157-2518.1000224
|View full text |Cite
|
Sign up to set email alerts
|

Status of Prostate Specific Antigen and Alpha Fetoprotein in Nigerian E-Waste Workers: A Cancer Risk Predictive Study

Abstract: Nigeria is reported as the largest electronic waste (e-waste) dump yard in Africa; and to date, Nigeria's e-waste management practices remain completely primitive. It was recently documented that the majority (88.8%) of Nigerian e-waste workers (with exposure burden of ≥ 6 hours per day; ≥ 6 days per week) worked without personal protective devices inspite of the volume of toxic substances, some of which are known carcinogens, documented to be found in e-waste. The present study aimed to evaluate the status of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…However, when soils are collected from contaminated dumpsites are used to fertilise plants, heavy metals present in the soil might affect the food chain through bioaccumulation leading to serious health issues in human. Health issues like blood disorder, kidney destruction, and brain and neurological damage may affect human during exposure to heavy metals [7]. More so, previous studies showed that consumption of dust and soils exposed to heavy metals and metalloid from hazardous waste, leaded petrol, automobiles and industrial waste may result to some ecological risk health issue [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, when soils are collected from contaminated dumpsites are used to fertilise plants, heavy metals present in the soil might affect the food chain through bioaccumulation leading to serious health issues in human. Health issues like blood disorder, kidney destruction, and brain and neurological damage may affect human during exposure to heavy metals [7]. More so, previous studies showed that consumption of dust and soils exposed to heavy metals and metalloid from hazardous waste, leaded petrol, automobiles and industrial waste may result to some ecological risk health issue [8].…”
Section: Introductionmentioning
confidence: 99%